Protein secretion in reduced genome strains from Streptomyces lividans TK24 - Marcelín Leyva, Clara Luz (Universidad Autónoma Metropolitana, 2019)
Genome reduction is a strategy that aims to improve the efficency of heterologous expression. Non-essential gene clusters from the secondary metabolism in S. lividans TK24, a common expression system, were deleted. The effect of this deletion on the expression and secretion for both native and heterologous proteins was not studied previously. In this work the native secretomes from ten reduced genome strains were characterized first. As a second step, monitoring heterologous protein secretion with mRFP allowed to know the effect of the genomic reduction on the expression and secretion of a heterologous protein by S. lividans TK24. Secreted monomeric Red Fluorescent Protein (mRFP) amounts considered low (strain R1.9: 9.235 ± 0.447 mg/gDCW) when compared with the wild type reported yields (61.551 ± 19.101 mg/gDCW) are reported. These values are seven to twenty-five times lower than the expected minimum. This suggests that, although the system has been previously proved as efficent for heterologous expression by Novakova et al. (2016), a different approach to study and understand the effect of the deletions in the cell’s metabolism and general functioning might be needed.